2011
DOI: 10.1038/nature10390
|View full text |Cite
|
Sign up to set email alerts
|

The genome of the green anole lizard and a comparative analysis with birds and mammals

Abstract: The evolution of the amniotic egg was one of the great evolutionary innovations in the history of life, freeing vertebrates from an obligatory connection to water and thus permitting the conquest of terrestrial environments1. Among amniotes, genome sequences are available for mammals2 and birds3–5, but not for non-avian reptiles. Here we report the genome sequence of the North American green anole lizard, Anolis carolinensis. We find that A. carolinensis microchromosomes are highly syntenic with chicken microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
662
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 598 publications
(701 citation statements)
references
References 23 publications
31
662
2
6
Order By: Relevance
“…We find novel evidence for a step‐wise pattern of northward diversification out of Florida, a sister–group relationship between two major mainland clades, and gene flow between Florida and the mainland. The individual sequenced by the Broad Institute for the green anole genome project was collected in South Carolina (Alföldi et al., 2011); future resequencing efforts should reveal if it is indeed representative of the rest of the species in terms of genomic structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find novel evidence for a step‐wise pattern of northward diversification out of Florida, a sister–group relationship between two major mainland clades, and gene flow between Florida and the mainland. The individual sequenced by the Broad Institute for the green anole genome project was collected in South Carolina (Alföldi et al., 2011); future resequencing efforts should reveal if it is indeed representative of the rest of the species in terms of genomic structure.…”
Section: Resultsmentioning
confidence: 99%
“…The green anole lizard ( Anolis carolinensis ) was the first nonavian reptile to have a complete genome sequence (Alföldi et al., 2011) and is an indispensable laboratory model for biomedical fields such as reproductive endocrinology (Lovern, Holmes, & Wade, 2004; Wade, 2012) and appendage regeneration (Hutchins et al., 2014). However, unlike studies using established models such as the house mouse ( Mus musculus ), which rely on inbred strains, green anole laboratory protocols are based on wild‐caught individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to HSA, whose smaller chromosomes sorted to both A and B groups, it is found that the larger chromosomes in GGA, TSC and CNI tend to have a lower than average GC content, whereas the smaller chromosomes have a higher than average GC content (figure 2a). ACA does not show this variation in GC content by chromosome size [11], suggesting that a common ancestor of bird, turtle and crocodile had two types of chromosomes correlated with chromosome size and GC content after divergence from the squamate ancestor. …”
Section: Discussionmentioning
confidence: 98%
“…ACA is 1.78 Gb in size with a 40.3 per cent total GC content according to the genome sequence data [11]. ACA has a few microchromosomes that are conserved between ACA and GGA, and that may have arisen in the reptile ancestor [11].…”
Section: Discussionmentioning
confidence: 99%
“…We next attempted to identify the Pax8 gene in the chicken genome; BLAST searches toward whole genome assemblies (version 2.1 available at the Ensembl Genome Browser; versions 3.0, 3.1, and 3.2 available at The Genome Institute of Washington University; International Chicken Sequencing Consortium, 2004) using both human, zebrafish, and mouse Pax8 peptide sequences as queries only identified the chick Pax2 and Pax5 loci previously annotated. We also analysed genome assemblies of other diaspid species (zebra finch, turkey, and anole lizard) available at Ensembl (Warren et al, 2010;Alfoldi et al, 2011) and garter snake genome sequences (Schwartz et al, 2010) as well as publicly available transcriptome sequences (Tzika et al, 2011). In all these searches, no Pax8 orthologous sequence could be placed into the Pax8 clade in the molecular phylogenetic tree (Fig.…”
Section: Pax8 Has Been Lost From the Chicken Genomementioning
confidence: 99%